Long-term treatment effect of a modified jailed-balloon technique for de Winter syndrome: a case report. Issue 5 (May 2020) - Du, Ji-Bing; Wang, Jia-Jia; Li, Wen-Yu; Huo, Xing-Yu; Li, Ya-Nan; Chen, Shu-Tao; Cong, Hong-Liang; Wu, Shao-Yuan; Wei, Yi-Liang
Timely recognition of the characteristic electrocardiographic pattern of de Winter syndrome is important for providing immediate reperfusion therapy for acute anterior myocardial infarction. In this case, an electrocardiogram showed 1- to 3-mm upsloping ST-segment depression at the J point in leads V1 to V6, with loss of R wave progression in leads V1 to V4. Urgent angiography showed occlusion of the proximal left anterior descending coronary artery and 70% stenosis in the ostial first diagonal branch (Medina type 1.1.1.). For this bifurcation lesion, we successfully performed a modified jailed-balloon technique to protect the side branch during percutaneous coronary intervention stenting. Thereafter, thrombolysis in myocardial infarction 3 flow was restored in both branches. This modified jailed-balloon technique is safe and effective in stent placement for de Winter syndrome without any loss of side branches.